The impact of foreign capital inflows on economic growth in selected west African countries - Musibau, Hammed Oluwaseyi; Hussin, Abdullah; Suraya, Mahmood; Suraya, Ismail; Hameed, Agboola Yusuf (2017)
Background: The West African countries have been identified with inadequate capital for investment, being one of the poorest subregions in the world. Objective: The objective of this study is to examine the nature of relationship between foreign capital inflows and the level of economic growth in selected West African Countries and to observe the causality between foreign capital inflows components and economic growth. Method: This study employed panel data from 1980 to 2015 to examine the impact of foreign capital inflows on the economic growth in the selected West African countries using Two Gap Theory. In addition, we adopt Pedroni cointegration and granger causality test. Result: The findings indicate shows the existence of long run relationship between foreign capital inflows and economics growth in selected West African country. All the variables were positive but only foreign direct investment is significant. Net migrant remittance, foreign direct investment and official development assistance cause growth in the short run. Conclusion: The study concludes that foreign capital inflows is imperative in closing the savings-investment gap required for economic growth in selected west African countries. Recommendation: The study recommends policy to encourage capital inflows via provision of enabling environment for foreign investment, reduction political instability and diversification of domestic economies.